2020
DOI: 10.46291/ijospervol7iss4pp1137-1163
|View full text |Cite
|
Sign up to set email alerts
|

What are Economic, Psychological and Social Consequences of the Covid-19 Crisis on Tourism Employees?

Abstract: This paper purposes to investigate the economic, psychological and social effects of the Covid-19 crisis on tourism employees in Turkey. The exploratory research approach was adopted and an online interview, one of the qualitative research methods, was used for data collection. This paper presents valuable evidence to contribute to the literature by emphasizing the effects of the Covid-19 pandemic on tourism employees. Tourism employees, who are the core of tourism employment, have been severely affected econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The above findings on the psychological changes add to the findings of other studies (e.g. Aguiar-Quintana et al, 2021;Brooks et al, 2020;Cao et al, 2020;Yin and Ni, 2021;Kang et al, 2020;Ozdemir, 2020), which pointed out the severity of impacts of COVID-19 pandemic on the mental health of the tourism workforces.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The above findings on the psychological changes add to the findings of other studies (e.g. Aguiar-Quintana et al, 2021;Brooks et al, 2020;Cao et al, 2020;Yin and Ni, 2021;Kang et al, 2020;Ozdemir, 2020), which pointed out the severity of impacts of COVID-19 pandemic on the mental health of the tourism workforces.…”
Section: Discussionsupporting
confidence: 86%
“…The powerful emotions experienced by the employees during the COVID-19 pandemic include fear, hopelessness, sadness, stress, anxiety, panic, depression, pensiveness and obsession (Aguiar-Quintana et al, 2021;Ozdemir, 2020;Sah et al, 2020). Such emotions can enhance insecurity (Habib et al, 2015;Trachik et al, 2018), hinder performance and satisfaction, and lead to job turnover (Jung et al, 2021).…”
Section: Psychological Impacts On the Workforcementioning
confidence: 99%
“…Consequently, from the perspective of tourism firms, government support has been invaluable (Gössling et al, 2020). A study conducted with tourism employees in Turkey revealed a plethora of government incentives, such as unemployment benefits, short-term working allowance, and unemployment benefit for suspended personnel, and support from firms, such as COVID-19 staff training, the supply of personal protective equipment, and hygienic working environments (Ozdemir, 2020). A study revealed the negative psychological impact of the COVID-19 crisis on tourism industry employees, impairing their well-being (Chen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that health and income are significantly related to experienced well-being (Killingsworth, 2021; Miret et al , 2017; Wolf et al , 2019). Recent COVID impact studies suggest that the loss of income, unemployment and increasing COVID health concerns have a profound impact on experienced well-being of tourism employees (Carnevale and Hatak, 2020; Mcguire et al ., 2021; Ozdemir, 2020) and their consumption sentiments and habits (Martin et al , 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Based on previous tourism research (Emen, 2020; Evans and Elphick, 2005; Hajibaba et al , 2015; Santana et al , 2003; Vargas-Sanchez, 2018), recent COVID-related studies (Carnevale and Hatak, 2020; Martins et al , 2020; Ozdimir, 2020; Sharma et al , 2021; Sigala, 2020), and postmodern behavioral economic theory (Ackerlof and Shiller, 2009; Kahneman, 2011; Katona, 1975; Manolis et al , 2001), this study proposes that the well-being of tourism employees, that is, the self-perception and sentiments of tourism employees, is disproportionately affected by the COVID-19 crisis as compared to nontourism employees. This study hypothesizes that the experienced well-being of tourism employees, in comparison to nontourism employees, is significantly more negatively affected by the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%